2021
DOI: 10.3390/cancers14010100
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Classifications of Early Gastric Cancer: A Literature Review

Abstract: Endoscopic technologies have been continuously advancing throughout the years to facilitate improvement in the detection and diagnosis of gastric lesions. With the development of different endoscopic diagnostic modalities for EGC, several classifications have been advocated for the evaluation of gastric lesions, aiming for an early detection and diagnosis. Sufficient knowledge on the appearance of EGC on white light endoscopy is fundamental for early detection and management. On the other hand, those superfici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
0
24
0
1
Order By: Relevance
“…Following years of research, a consensus on the utility of endoscopy for gastric cancer diagnosis has been reached, along with recommendations to reduce Helicobacter pylori infections, take sufficient exercise and follow a healthy lifestyle (18). The early detection of gastric cancer increases the likelihood of treatments being effective (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Following years of research, a consensus on the utility of endoscopy for gastric cancer diagnosis has been reached, along with recommendations to reduce Helicobacter pylori infections, take sufficient exercise and follow a healthy lifestyle (18). The early detection of gastric cancer increases the likelihood of treatments being effective (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has distinct limitations: considerable is required for image acquisition, there is a steep learning curve associated with image interpretation, and the required equipment is typically available only at tertiary care centers (46). Endocytoscopy (EC) is one of the most sophisticated current techniques, based on ultra-high magnification endoscopy, and allows the in vivo microscopic visualization of the surface level of mucosal cells with the use of stains (8,47). Fourth-generation endocytoscopes support 500× continuous zoom-focus magnification, and the average time needed to conduct EC is approximately 10-20 minutes (48).…”
Section: Endoscopic Diagnosismentioning
confidence: 99%
“…Fourth-generation endocytoscopes support 500× continuous zoom-focus magnification, and the average time needed to conduct EC is approximately 10-20 minutes (48). Standardized classification criteria for EC-detected stomach cancer are not yet in place; however, in another study, Inoue Haruhiro et al (8,48,49) developed a simple, three-level, classification of EC-detected colorectal lesions (50): non-neoplastic lesions are classified as EC1, adenoma is classified as EC2, and carcinoma is classified as EC3 (8). Furthermore, they identified an "enlarged nuclear sign"(ENS) as a distinct characteristic of gastric adenocarcinomas and reported that the sensitivity, specificity, and accuracy of ENS for the diagnosis of EGC were 84.8%, 90.0%, and 87.2%, respectively (49).…”
Section: Endoscopic Diagnosismentioning
confidence: 99%
“…Gastric cancer (GC), as one of the most common malignant tumors in the world, ranks the fifth most diagnosed cancer worldwide [ 1 ]. Nowadays, several therapeutic strategies have been reported to be effective in the treatment of GC patients, including surgical treatment, chemotherapy, and immunotherapy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%